A study on factors influencing profitability of Islamic banks in Malaysia / Hasmidah Takedir - Takedir, Hasmidah (2015)
This paper is made to find out about the factors that influence the Islamic banks profitability in Malaysia. By using the secondary data for analysis retrieved from the Islamic Banks official website, the sample of this study comprises of 5 local Islamic banks in Malaysia on over seven years period from 2008 to 2014. Methodology used for this study is by using the Multiple Linear Regression with panel data. In this study, the dependent variable is the Islamic banks profitability which is return on asset (ROA). While, the independent variables are the factors that influence the Islamic banks profitability. Based on the variables, the study aims to explore the influence of the internal banks characteristics of bank size, operating efficiency, and capital adequacy influence to the bank’s profitability of return on asset (ROA). Therefore, it highlights the most internal banks characteristics influence on the profitability of Islamic banks. This result of the study shows that the operating efficiency and capital adequacy ratio have positively influence the Islamic banks profitability in Malaysia. While Bank Sizes has negatively influence towards the Islamic banks profitability in Malaysia. Finally, the factors of internal banks characteristics positively influence the Islamic banks in Malaysia.